A simple Ce-doping strategy to enhance stability of hybrid symmetrical electrode for solid oxide fuel cells. (30th October 2020) - Song, Kai; Yu, Zhipeng; Luo, Xiaoyan; Zhu, Shiyue; Yang, Yang; Yang, Quan; Tian, Dong; Lu, Xiaoyong; Ding, Yanzhi; Chen, Yonghong; Lin, Bin
Abstract: Symmetrical solid oxide fuel cell (SSOFC) is a simple and very promising cell for the rest of the most important commercialization process, which has been longing for stable and efficient symmetrical electrodes, from single-phase perovskites to reducible perovskites with in-situ exsolved metal nanoparticles. Herein, we present a new-type hybrid symmetrical electrode consisting of two different perovskite phases for SSOFC, which interact by dynamic compositional change and accordingly improve the electrochemical activity. Furthermore, a simple Ce-doping strategy is successfully developed to solve the redox stability issue of the hybrid symmetrical electrode for SSOFC. Typical Gd0.65 Sr0.35 Co0.25 Fe0.75 O3-δ (GSCF) consisting of a cubic perovskite phase and an orthorhombic perovskite phase is chosen as a proof-of-concept. Gd0.65 Sr0.35 (Co0.25 Fe0.75 )0.9 Ce0.1 O3-δ (Ce-GSCF) with an optimized Ce content of only 10% exhibit the enhanced chemical and thermal stability, consisting of a cubic perovskite phase, an orthorhombic perovskite phase and an in-situ exsolved cubic fluorite phase (GDC). More importantly, Ce-GSCF exhibits very high stability in H2 at 700 °C and a dramatical reduction of averaged thermal expansion coefficient from 19.5 × 10 −6  K −1 to 16.4 × 10 −6  K −1 . The single-cell with Ce-GSCF hybrid symmetrical electrode reaches a high maximum power density of 224 mW/cm 2 at 700 °C, and can work stably for 180 h without any degradation, indicating that the simple Ce-doping strategy is promising to improve stability of hybrid symmetrical electrode for SOFCs. Highlights: A new-type hybrid symmetrical electrode is proposed for SOFCs. A simple Ce-doping strategy is developed to enhance redox stability. Ce doping dramatically reduced thermal expansion. Ce-GSCF electrode exhibited high ORR and HOR activities. SSOFCs with Ce-GSCF electrodes showed 180-h long-term stability.